"Ábrándok bűvöletében" - környezetfilozófiai olvasat - Tóth I., János (Kultúratudományi Szemle, 2024)
"Under the Spell of Illusions” – An Environmental Philosophy Interpretation András Gelencsér's book ("Under the Spell of Illusions: The Limits of Sustainable Development") draws attention to the following environmental dilemma. Societies can only sustain themselves by continuously using the earth's natural materials and energy resources. However, these material resources („canned food”) will run out within 15-25 years. Therefore, the spread of renewable energy harnessing devices (solar panels, wind turbines) does not reduce but rather exacerbates the environmental crisis. This conclusion contradicts both the growth-centric modern mainstream and the green thinking focusing on renewable energies. My study analyses the environmental philosophy aspects of this problem.